Surface activation of poly(methyl methacrylate) by plasma treatment : stable antibody immobilization for microfluidic enzyme-linked immunosorbent assay - Darain, Farzana (2013)
With the aim of obtaining stable antibody immobilization on the poly(methyl methacrylate), PMMA channel surface, PMMA substrates were activated with O2 plasma treatment to introduce surface polar groups on it. The plasma-treated PMMA surfaces were characterized using water contact angle measurement, atomic force microscopy (AFM), and X-ray photoelectron spectroscopy (XPS). It was observed that plasma treatment significantly improved the surface wettability with changing surface chemistry and topography. The strategy of immobilization of a model antibody, anti-goat IgG on plasma-treated PMMA involved two steps. First the plasma-treated PMMA was functionalized with (3-aminopropyl)thriethoxy silane, APTES off-chip which facilitated covalent capturing of antibody via a crosslinking agent in the inner surface of PMMA channel in the second step. The antibody immobilization on plasma-treated PMMA was also confirmed using AFM, XPS, and fluorescence microscopy. The anti-IgG covalently captured on channel surface was evaluated with sandwich ELISA protocol on-chip using fluorescence microscopy. The observed results demonstrate that this technique could be extended to integrate the current diagnostic techniques into the plastic chip for important biomarker diagnosis.